Antithrombotic treatment for secondary prevention of stroke and other thromboembolic events in patients with stroke or transient ischemic attack and non-valvular atrial fibrillation: A European Stroke Organisation guideline. (September 2019) - Klijn, Catharina JM; Paciaroni, Maurizio; Berge, Eivind; Korompoki, Eleni; Kõrv, Janika; Lal, Avtar; Putaala, Jukka; Werring, David J
Patients with ischemic stroke or transient ischemic attack and non-valvular atrial fibrillation have a high risk of recurrent stroke and other vascular events. The aim of this guideline is to provide recommendations on antithrombotic medication for secondary prevention of stroke and other vascular outcomes in these patients. The working group identified questions and outcomes, graded evidence, and developed recommendations according to the Grading of Recommendations Assessment, Development, and Evaluation approach and the European Stroke Organisation (ESO) standard operating procedure for guidelines. The guideline was reviewed and approved by the ESO guideline board and the ESO executive committee. In patients with atrial fibrillation and previous stroke or transient ischemic attack, oral anticoagulants reduce the risk of recurrence over antiplatelets or no antithrombotic treatment. Non-vitamin K antagonist oral anticoagulants are preferred over vitamin K antagonists because they have a lower risk of major bleeding and death. Recommendations are weak regarding timing of treatment, (re-)starting oral anticoagulants in patients with previous intracerebral haemorrhage, and treatment in specific patient subgroups of those of older age, with cognitive impairment, renal failure or small vessel disease, because of a lack of strong evidence. In conclusion, for patients with atrial fibrillation and ischemic stroke or transient ischemic attack, non-vitamin K antagonist oral anticoagulants are the preferred treatment for secondary prevention of recurrent stroke or thromboembolism. Further research is required to determine the best timing for initiating oral anticoagulants after an acute ischemic stroke, whether or not oral anticoagulants should be (re)started in patients with a history of intracerebral haemorrhage, and the best secondary preventive treatment in specific subgroups.